Death Following Liver Transplantation in a Child with Crigler-Najjar Syndrome Type I: A Case Report - Ida Soghi; Mohammad Sobhani Shahmirzadi; Hamid Pashah Soltan; Samira Saeedi; Leila Jouybari (Journal of Clinical and Basic Research, 2017)
Introduction: Crigler-Najjar syndrome is a rare autosomal recessive genetic disorder with incidence rate of one per a million live births. This syndrome often causes permanent damage to the nervous system due to high bilirubin level. We hereby present a child with Crigler-Najjar syndrome type I (CNS-I). Case description: The patient was an 18-month-old male infant referred to Taleghani Hospital in Gorgan due to jaundice at the first week of birth. CNS-I was confirmed by detecting high level of non-conjugated bilirubin. The patient was the second child of a consanguineous marriage (between cousins). The first child of the family was aborted in the first pregnancy due to infection. The patient underwent liver transplantation at age of six months. Renal and kidney ultrasound showed no abnormality. The patient was hospitalized several times due to fever and rectorrhagia following the liver transplantation, and eventually died of lymphoproliferative disorder. Conclusions: Early diagnosis at birth and therapeutic interventions including liver transplantation in the early months after birth could prevent the most common and dangerous complication of the disease, kernicterus. Therefore, early diagnosis and follow-up are of great importance in patients’ survival. Moreover, genetic counseling should be provided for consanguineous couples.